Nutritional and Industrial Insights into Hemp Seed Oil: A Value-Added Product of Cannabis sativa L. - Aggeliki Mygdalia; Ioannis Panoras; Eirini Vazanelli; Eleni Tsaliki (Seeds)
Industrial hemp is mainly cultivated for its fibers aimed at the production of textiles, paper, and cordage; the inflorescences for medicinal purposes; and the seeds are used by the food industry due to their high nutritional and functional matrix of protein, fiber, lipids, and microelements. Hemp seed oil (HsO) is a unique source of polyunsaturated fatty acids, with a phenomenal ω6:ω3 ratio of 2.5–3.0, significantly enhancing human health when consumed daily. HsO is mostly obtained through cold pressing due to minimal thermal treatment, and although of lower yield compared to solvent extraction, it presents higher quality lipid fractions and organoleptic characteristics such as color, taste, flavor, and density. Although HsO is a powerful source of polyunsaturated fatty acids, antioxidants, and phytosterols, its production lacks standardized quality control parameters, except for THC, which is subject to EU legislation. Therefore, it is essential to build up a quality protocol system for standardizing seed conservation, oil extraction methods, and quality parameters. This review aims to display an overall nutritional framework of the HsO and encourage further research into its use in the food value chain.